History and politics of mental health policy and care in South Africa - Sharon Kleintjes; Marguerite Schneider (Elsevier, 2023)
This paper starts with a broad historical overview of the influence of colonial rule on shaping the racialised and socio-economic environment which predated and persisted into the adoption of formal apartheid practices, and the mental health and wellbeing related impacts on the people of South Africa. This is followed by a review of policy and service developments within the past 25 years of post apartheid democratic rule in South Africa. Some of the successes and failures of the different policies provided in South Africa are explored. The paper concludes with some emerging trends in policy and practice that will need attention in the coming decades as we seek to improve the mental wellbeing of South Africans, including South Africans living with mental disorders. The paper extrapolates key points of relevance from the South African experience to other contexts experiencing the mental health related impact of colonialism and other current forms of oppression, including ableism, gender discrimination, and others.